Differences in lower-limb coordination and coordination variability between novice and experienced runners during a prolonged treadmill run at anaerobic threshold speed - Mo, S.; Chow, D. H. K. (Journal of Sports Sciences, 2019)
This study investigated differences in lower-limb coordination and coordination variability between experienced and novice runners during a prolonged run. Thirty-four participants were categorised as either experienced (n = 17) or novice runners (n = 17). All participants performed a 31-min treadmill run at their individual anaerobic threshold speed, and lower-limb kinematic data were acquired in the sagittal plane at the beginning, middle, and end of the run. Lower-limb coordination and variability during the stance phase were quantified using a vector coding technique for hip-knee, knee-ankle, pelvis-thigh, thigh-shank, and shank-foot couplings. Repeated-measure analysis of covariance revealed that running experience and time had significant interactions on the coordination patterns for hip-knee and pelvis-thigh couplings. During the midstance, experienced runners exhibited a higher percentage of in-phase motion for pelvis-thigh and knee-ankle couplings while novice runners displayed a higher percentage of distal motion for pelvis-thigh coupling and anti-phase motion for hip-knee coupling. Experienced runners displayed more variability in hip-knee and shank-foot couplings, and novice runners had more variability in hip, knee, and thigh motion. Experienced and novice runners adapted to progressive fatigue through different lower-limb coordination patterns. Throughout the prolonged run, experienced runners demonstrated greater coordination variability and novice runners displayed greater joint and segment variability.